Peran dan Pentingnya Komunikasi dalam Implementasi Kawasan Tanpa Rokok di Kota Medan - Nadila Savira; Indriani Indriani; Deandra Almaz Zahra Nasution; Aisyah Putri; Rayhan Irwanda (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to determine the role and importance of communication in implementing the smoke-free area policy in the city of Medan. National research is descriptive research, data collection techniques are carried out by reviewing the literature through collecting secondary data from relevant scientific and international journals. Data analysis uses data reduction techniques, data presentation and drawing conclusions. The results of the research show that communication in implementing the smoke-free area policy in the city of Medan has been implemented through outreach efforts or using the media, but has not worked optimally. Communication is an important aspect and indicator in the success of a public policy. Communication plays a very important role in disseminating policies and information, transmitting information, creating partnerships between policy makers and the public, gaining public support, expanding information, maintaining information ethics so as to avoid distorted information. and expanding coordination. Communication also plays a very important role in policy because it helps policy implementers know what must be done, explains the responsibilities and rights of the community so that it encourages the community to implement the smoke-free area policy in the city of Medan.